Study on eco-efficiency optimization based on LCA-MFCA integration method: a case study on the cement industry - Liu, Sanhong; Xie, Ying; Liang, Wen; Liu, Tieqiao; Luo, Shanmei (Sage, 2025)
Cement production in China suffers from low eco-efficiency due to high coal and electricity consumption and substantial emissions. This study proposes a novel approach integrating Life Cycle Assessment (LCA) and Material Flow Cost Accounting (MFCA) to improve both economic and environmental performance. The method includes: (1) quantifying material, economic, and environmental losses using LCA and MFCA; (2) identifying improvement strategies through Pareto analysis, hypothesis testing, and expert input; and (3) validating results using an empirical case study. Applied to a cement company in Xinjiang, the approach increased eco-efficiency from 0.8737 to 1.0519, demonstrating synchronous economic and environmental gains. This is one of the first studies to apply LCA–MFCA integration in China’s cement sector.
Keywords: eco-efficiency; material flow cost accounting; life cycle assessment; cement industry; 4104 Environmental Management; 33 Built Environment and Design; 38 Economics; 40 Engineering; 41 Environmental Sciences; 4005 Civil Engineering; 3302 Building; 12 Responsible Consumption and Production; Development Studies